Standing in customers’ shoes: How responsible leadership inhibits unethical pro-organizational behavior - Cheng, Ken; Guo, Limin; Lin, Yinghui; Hu, Panpan; Hou, Changchang; He, Jiaying (Frontiers in Psychology, 2022)
Although the negative impact of responsible leadership on employees’ unethical pro-organizational Although the negative impact of responsible leadership on employees’ unethical pro-organizational behavior has been documented in the literature, little is known about its underlying processes and boundaries. Drawing on social information processing theory and social learning theory, we built a moderated mediation model to explain why and when unethical pro-organizational behavior could be inhibited by responsible leadership. We conducted a two-phase questionnaire survey to collect data. The empirical results based on the sample of 557 Chinese salespeople showed that customer-oriented perspective taking partially mediated the negative link between responsible leadership and unethical pro-organizational behavior and that leader competence strengthened the direct effects of responsible leadership on customer-oriented perspective taking and unethical pro-organizational behavior as well as the indirect effect of responsible leadership on unethical pro-organizational behavior via customer-oriented perspective taking. These findings enrich the current understanding of how responsible leadership relates to unethical pro-organizational behavior, extend the limited literature on customer-oriented perspective taking, and offer some suggestions that managers can follow to inhibit unethical pro-organizational behavior. Limitations and future research directions are also discussed.